Analysis of the current situation of the development of virtual reality environments for the teaching of industrial automation systems (LACCEI, 2024)
Virtual Reality (VR) can be described as a set of technologies involved in positioning the user in an environment simulated by a computer, which allows them to interact with three-dimensional objects found in the virtual environment. Within virtual environments there are a number of tools, the main ones being VR glasses [1], accompanied by audio devices and motion sensors that provide the user with a more immersive experience. According to the perspectives developed by the authors, the industries and educational centers that implement virtual environments for teaching can have advantages in terms of personal training and in minimizing costs of implementing physical training scenarios. The analysis of different approaches to the use of VR in the development of industrial applications, through selected research, will provide the ability to broaden the spectrum of possibilities in the field of automation systems in the present and future. In the present work, a review of the existing literature is carried out from different types of perspectives and applications on the use of simulated environments and how they can be a source of learning and improvement of different activities linked to control and automation systems.